2023
DOI: 10.1021/acsanm.3c03138
|View full text |Cite
|
Sign up to set email alerts
|

FeOOH Quantum Dot-Coupled Z-Scheme BiVO4/g-C3N4 Heterojunction for Enhancing Photo-Fenton Reactions

Rui Liu,
Ru Li,
Lei Yang
et al.

Abstract: Herein, FeOOH quantum dots and a Z-scheme BiVO 4 /g-C 3 N 4 catalyst were coupled to obtain a Z-scheme heterojunction for photo-Fenton reactions to facilitate the transport of electrons and the generation of radicals. The obtained materials exhibited better visible light-driven photo-Fenton degradation of Rhodamine B, which is 22.06 times as high as pure BiVO 4 , 18.65 times as high as pure g-C 3 N 4 , and 3.44 times as high as BiVO 4 /g-C 3 N 4 , showing great potential in photo-Fenton degradation of pollutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 71 publications
(91 reference statements)
0
7
0
Order By: Relevance
“…The survey spectra of g-C 3 N 4 , IT, and CIT are shown in Figure S5. The O 1s spectrum of IT can be fitted to three peaks (Figure a), corresponding to lattice oxygen (529.45 eV), surface hydroxyls (531.61 eV), and adsorbed water (533.24 eV), respectively. , The strong peaks of surface hydroxyls and adsorbed water are attributed to the abundant oxygen vacancies in IT that can adsorb hydroxyl groups and water on the surface of IT. ,, Compared to IT, the hybrid CIT1 sample displays an increase in the hydroxyl peak and a decrease in the lattice oxygen peak (Figure a). This change may indicate that more oxygen vacancies were generated in the CIT1, potentially from reduction by cyanamide under a N 2 atmosphere during pyrolysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The survey spectra of g-C 3 N 4 , IT, and CIT are shown in Figure S5. The O 1s spectrum of IT can be fitted to three peaks (Figure a), corresponding to lattice oxygen (529.45 eV), surface hydroxyls (531.61 eV), and adsorbed water (533.24 eV), respectively. , The strong peaks of surface hydroxyls and adsorbed water are attributed to the abundant oxygen vacancies in IT that can adsorb hydroxyl groups and water on the surface of IT. ,, Compared to IT, the hybrid CIT1 sample displays an increase in the hydroxyl peak and a decrease in the lattice oxygen peak (Figure a). This change may indicate that more oxygen vacancies were generated in the CIT1, potentially from reduction by cyanamide under a N 2 atmosphere during pyrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…49,50 The strong peaks of surface hydroxyls and adsorbed water are attributed to the abundant oxygen vacancies in IT that can adsorb hydroxyl groups and water on the surface of IT. 43,51,52 Compared to IT, the hybrid CIT1 sample displays an increase in the hydroxyl peak and a decrease in the lattice oxygen peak (Figure 5a). This change may indicate that more oxygen vacancies were generated in the CIT1, potentially from reduction by cyanamide under a N 2 atmosphere during pyrolysis.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The construction of hybrid catalysts in the Z-scheme heterojunction has been demonstrated as an effective strategy for improving photocatalytic performance by efficient electron–hole separation and increased redox capability. In designing such heterojunctions, metal oxides, graphitic compounds, and MOFs are commonly accompanied. ,, Implementing the Z-scheme requires the selection of photocatalysts with suitable band energy for efficient generation of •O 2 – and •OH – radicals. , Especially, the heterojunction composed of a bimetallic MOF is more complex to understand the catalytic mechanism and its applicability. , …”
Section: Introductionmentioning
confidence: 99%
“…Various studies can be found in the literature on the kinetics of photocatalytic and photo-Fenton degradation of pollutants. Generally, photo-Fenton degradation follows pseudo-first-order kinetics, wherein the production of major reaction radicals gets accelerated due to the redox reaction of Fe or Fe-like species. Instead, the kinetics of photocatalysis can encompass a range of behaviors, including pseudo zero-order, pseudo-first-order, or pseudo-second-order reactions .…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the kinetics of photocatalysis can encompass a range of behaviors, including pseudo zero-order, pseudo-first-order, or pseudo-second-order reactions . For example, FeOOH coupled with the heterostructure of BiVO 4 /GC 3 N 4 exhibited pseudo-first-order kinetic degradation of TC . However, Ma et al reported a second-order TCH degradation kinetics for Ag/TiO 2 catalyst .…”
Section: Introductionmentioning
confidence: 99%